Pengaruh Efikasi Diri dan Motivasi Terhadap Keberhasilan Usaha Kafe di Kecamatan Tanjung Morawa - Teranova, Ferryna Fiki; Siregar, Dahrul (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Indonesia is a nation with vast and abundant natural resources, making it worthy of being recognized as a country rich in both natural and human resources. These resources have the potential to bring significant benefits to Indonesia's economy. However, this potential has not been fully realized due to the country's inability to utilize its wealth efficiently. The purpose of this study is to determine the effect of self-efficacy on the success of café businesses in Tanjung Morawa District and to examine the influence of motivation on the success of café businesses in the same area. The independent variables in this study are self-efficacy and motivation, while the dependent variable is business success. The study utilizes a sample of 30 cafés operating in Tanjung Morawa District. The findings indicate that the self-efficacy variable has a positive and significant effect on the success of café businesses in Tanjung Morawa District. Additionally, motivation also has a positive and significant impact on the success of café businesses in the district.